The Messy Side of the Enlightenment: Eighteenth-Century Translators, Reviewers, and the Traces They Left Behind. Issue 4 (1st October 2020) - Tautz, Birgit
Abstract: This article looks at the "messy side" of Enlightenment, treating periodicals as a major index of this messy side. While periodicals have been relegated to ancillary role in understanding autonomous aesthetics, canonical literature and the public sphere, I examine them from a different angle. By working with the database Zeitschriften der Aufklärung, digital humanities and conventional reading methods, I relate "translation" and "review" to one another, and to questions about original authorship, as well as small or domineering genres of literature. The article shows that, by looking beyond causal relationships and instead paying attention to the traces that translators and reviewers left behind in periodicals, we can gain new insights into the broad, and messy, contours of reading and the Enlightenment public sphere.